2015
DOI: 10.1007/978-3-319-24027-5_46
|View full text |Cite
|
Sign up to set email alerts
|

LifeCLEF 2015: Multimedia Life Species Identification Challenges

Abstract: Abstract. Using multimedia identification tools is considered as one of the most promising solutions to help bridge the taxonomic gap and build accurate knowledge of the identity, the geographic distribution and the evolution of living species. Large and structured communities of nature observers (e.g., iSpot, Xeno-canto, Tela Botanica, etc.) as well as big monitoring equipment have actually started to produce outstanding collections of multimedia records. Unfortunately, the performance of the state-of-the-art… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
50
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 83 publications
(55 citation statements)
references
References 41 publications
(25 reference statements)
1
50
0
Order By: Relevance
“…This is still far from matching the scale and variety of existing general major datasets for images [52,55,51], videos [53] or languages [54]. In addition, we can see that the PlantClef2015 dataset [6] has one of the largest number of object categories but the least number of images. For example, compared to the ILSVRC 2010 dataset [55], it has less than 10 % of their total images but the M A N U S C R I P T same number of categories.…”
Section: Methodsmentioning
confidence: 94%
See 3 more Smart Citations
“…This is still far from matching the scale and variety of existing general major datasets for images [52,55,51], videos [53] or languages [54]. In addition, we can see that the PlantClef2015 dataset [6] has one of the largest number of object categories but the least number of images. For example, compared to the ILSVRC 2010 dataset [55], it has less than 10 % of their total images but the M A N U S C R I P T same number of categories.…”
Section: Methodsmentioning
confidence: 94%
“…Classification performance of the network trained with all training sets (w = 2,288, P = 34,672) is obviously better compared to that trained on smaller subset of data (W = 1,324, P = 3,960). Next, although reducing CNN layer depth might affect A C C E P T E D M A N U S C R I P T [52] 8.3 milion 365 Sport-1M [53] 1 milion 487 Visual Genome QA [54] 1.7 million questions/answer pairs -ILSVRC 2010 [55] 1.4 milion 1000 PlantClef2015 dataset [6] 113,205 1000…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…In the 2015 SeaClef contest [23], the best results have shown that Deep Learning can achieve a better classification for fish detection than SVM or other classical methods. This may be due to the fact that in Deep Learning, features are automatically built by the classifier itself, in an optimal way.…”
Section: Introductionmentioning
confidence: 99%